Respostas
respondido por:
4
x²-2x-8=0
a=1
b=-2
c=-8
Δ = b² - 4 . a . c
Δ = (-2)² - 4 . 1 . (-8)
Δ = 4 +32
Δ = 36
x = - b ±√Δ / 2a
x = - (-2) ±√36 / 2.1
x = 2 ± 6 / 2
x' = 2 + 6 / 2
x' = 8/2
x' = 4
x" = 2 - 6 / 2
x"= -4/2
x"= -2
Os números -2 e 4 são raízes da equação.
a=1
b=-2
c=-8
Δ = b² - 4 . a . c
Δ = (-2)² - 4 . 1 . (-8)
Δ = 4 +32
Δ = 36
x = - b ±√Δ / 2a
x = - (-2) ±√36 / 2.1
x = 2 ± 6 / 2
x' = 2 + 6 / 2
x' = 8/2
x' = 4
x" = 2 - 6 / 2
x"= -4/2
x"= -2
Os números -2 e 4 são raízes da equação.
ollo:
Por nada. Disponha.
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás